2008
DOI: 10.1063/1.3033390
|View full text |Cite
|
Sign up to set email alerts
|

Indentation-induced tin whiskers on electroplated tin coatings

Abstract: The indentation-induced growth of tin whiskers/hillocks was observed for the tin coatings over copper substrate. There existed multiple tin whiskers/hillocks surrounding the indents in contrast to only a few whiskers/hillocks in the nonindented area. The number of the tin whiskers surrounding the indents increased with the increase in the indentation load and decreased with the increase in the thickness of the tin coatings. The formation and growth of the tin whiskers were due to the pressure gradient at the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The above described buckling yields a significant deflection λ < ∼ l. The results in Eqs. (12) and (13) coincide with that of exact analysis 21,22 to the accuracy of numerical coefficients of the order of unity.…”
Section: Uniform Whiskerssupporting
confidence: 68%
“…The above described buckling yields a significant deflection λ < ∼ l. The results in Eqs. (12) and (13) coincide with that of exact analysis 21,22 to the accuracy of numerical coefficients of the order of unity.…”
Section: Uniform Whiskerssupporting
confidence: 68%
“…It was inferred also that the stress gradients can be more im-portant than stresses itself. [30][31][32][33] Unfortunately, these approaches lack predictive power providing no estimates for whisker growth rates and parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Another important driving force for whisker growth is mechanically applied stress on the Sn sample. Numerous studies have investigated the application of mechanical stress using different loading devices, such as a clamping fixture, 21,36,58 three-point or four-point bending [59][60][61] of Sn-coated strips, micro-indentation, [62][63][64][65] and in situ nanoindentation. 66,67 Fisher et al, 21 using a ring clamp (shown in Fig.…”
Section: Externally Applied Mechanical Stressmentioning
confidence: 99%